2014
DOI: 10.1371/journal.pone.0102465
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Osteopathic Treatment on Pain in Adult Patients with Cystic Fibrosis – A Pilot Randomized Controlled Study

Abstract: BackgroundPain is a common complication in patients with cystic fibrosis (CF) and is associated with shorter survival. We evaluated the impact of osteopathic manipulative treatment (OMT) on pain in adults with CF.MethodsA pilot multicenter randomized controlled trial was conducted with three parallel arms: OMT (group A, 16 patients), sham OMT (sham treatment, group B, 8 patients) and no treatment (group C, 8 patients). Medical investigators and patients were double-blind to treatment for groups A and B, who re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
1
6
0
7
Order By: Relevance
“…2,3,19,21, 25,27,37 Current guidelines have suggested that efforts to minimize some causes of pain are within the scope of physiotherapy practice, which may include physical modalities. 1,35 Whilst this may incorporate manual treatment and exercises for optimal posture, mobility and muscle function, 1,32,38 40 options (including the use of heat and ice) and psychological interventions (distraction, relaxation, mindfulness and counselling) are also warranted. Further study is required to determine the most effective treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,19,21, 25,27,37 Current guidelines have suggested that efforts to minimize some causes of pain are within the scope of physiotherapy practice, which may include physical modalities. 1,35 Whilst this may incorporate manual treatment and exercises for optimal posture, mobility and muscle function, 1,32,38 40 options (including the use of heat and ice) and psychological interventions (distraction, relaxation, mindfulness and counselling) are also warranted. Further study is required to determine the most effective treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Eine einzige prospektive Pilotstudie zeigte eine Reduktion von Gelenkschmerzen und Angst durch regelmäßige Yogastunden [28]. Eine RCT zur Osteopathie fand einen nichtsignifikanten Rückgang von Thorax-und Rückenschmerzen [15]. Es erfolgte stets eine resistogrammgerechte antibiotische Therapie, Atemphysio-und Inhalationstherapien.…”
Section: Methodenunclassified
“…In den von uns erfassten Studien, die auch in der aktuellen Übersichtsarbeit von Trandafir et al enthalten sind [32] Therapieoptionen wie Yoga und Osteopathie wurden auch prospektiv geprüft (s. unten) [15,20].…”
Section: Ergebnisse -Stand Der Wissenschaftunclassified
“…Zusätzlich versuchen sich einige Patienten in alternativen Strategien und Therapieansätzen, die von Homöopathie über Akupunktur bis zu physikalischen Maßnahmen (Ruhe oder Aktivität, Wärme oder Kälte, Yoga und Meditation, Osteopathie) reichen [15,20,30,32]. Hier existieren wenige prospektive Studien zu Wirksamkeit und Effektivität.…”
Section: Ergebnisse -Stand Der Wissenschaftunclassified